Novel Platinum II and Platinum IV Complexes Exhibit An Anti-Neoplastic Potential Against A549 Cancer Cell Line - Baz, Joy (2021)
Lung cancer is considered as the leading cause of cancer death and the second most diagnosed type of cancer. Although platinum-based chemotherapeutic drugs were relatively successful in treatment of lung cancer, patients frequently suffer from severe side effects, resistance and overall toxicity. This has lead scientists to invest in the discovery of novel platinum complexes that would improve efficacy and overcome toxicity. The present study aims to test the anti-neoplastic activity of novel Pt II and Pt IV complexes against A549 lung cancer cells and elucidate the mechanism of action involved. Cell cytotoxicity assay was conducted 72hrs post-treatment on A549 and mesenchymal stem cells using WST-1 kit. Cellular uptake of platinum complexes was studied by ICP-MS. Cell death analysis was studied using flow cytometry. Western blots were conducted to assess modulation of cell apoptotic markers. Free radical production was measured using reactive oxygen species kit. DNA degradation was evaluated by the comet assay. Results showed that Pt II and Pt IV complexes selectively reduce lung cancer cell viability. Cellular uptake results suggest a time-dependent active mode of transport for both complexes with Pt II being transported at higher rates and concentrations when compared to Pt IV. Flow cytometry revealed significant cell death by apoptosis and western blots showed the upregulation of intrinsic apoptotic markers. Treatment with Pt II and Pt IV also showed significant amounts of free radical production and increased DNA damage. In conclusion, Pt II and Pt IV complexes induce lung cancer cell apoptosis through an intrinsic pathway and may be considered as promising selective and efficient anticancer drugs.